A classification scheme for open government data: towards linking decentralised data. (21st June 2011) - Kalampokis, Evangelos; Tambouris, Efthimios; Tarabanis, Konstantinos
Open government data (OGD) refers to making public sector information freely available in open formats and ways that enable public access and facilitate exploitation. Lately, a large number of OGD initiatives launched worldwide aiming to implement one-stop portals acting as single points of access to governmental data. At the same time, the so-called linked data technologies emerged aiming at publishing structured data on the web in such a way that enables semantically enriching data, uniform access to data, and linking of data. In this paper, we first propose a classification scheme for OGD initiatives based on the relevant literature. We thereafter, review and analyse OGD initiatives based on the proposed scheme. We finally present an architecture and prototype implementation for the most advanced OGD class in our scheme, which enables linking decentralised data.